School motivation through the use of information and communication technologies (ICT) - Delgado, José Gregorio Lucas; Moreno, José Alberto Vigueras (International research journal of management, IT and social sciences, 2020)
School motivation is a process that includes aspects of cognitive and affective type, related to the teaching-learning process, which involves the school trilogy (educators, students and parents) who participate dynamically and actively in academic development. This research was intended to demonstrate that teachers can motivate students in the teaching-learning process under the potential of Information and Communication Technologies to achieve the activation of cognitive resources, since currently, it can be counted with different applications that are very useful at the time of teaching, making use of innovation, leaving aside the traditionalism where the teacher was the protagonist and giving that role to the student, digital native. Finally, it is evident how the student, being motivated by his teacher, manages to pass the different barriers that may arise in the realization of the educational activities, being necessary that the educator is constantly motivating and giving merits to the students, even if he does not comply the established parameters, offering them new strategies so that they can fulfill the proposed activities.